The Influence of Green Marketing and Environmental Concern on Green Purchase Intention (Case Study of Traditional EB Batik) - Raju Rifai; May Dedu; Tiara Muthiarsih (Publikasi Indonesia, 2026)
This study aimed to analyze the influence of green marketing and environmental concern on green purchase intention among EB Batik consumers. This study used a quantitative method with an associative approach, involving 218 respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the assistance of SPSS software. The results showed that green marketing had a positive and significant effect on green purchase intention, with a significance value of 0.000 < 0.05, while environmental concern had a negative and significant effect, with a significance value of 0.011 < 0.05. Simultaneously, both variables had a significant effect on green purchase intention, with an adjusted R-square value of 0.666, indicating that 66.6% of the variation in green purchase intention could be explained by green marketing and environmental concern.